TEST SYSTEM BASED ON ROOT EXUDATES FOR HIGH-YIELDING COMMON BUCKWHEAT ( FAGOPYRUM ESCULENTUM MOENCH.) FORM SCREENING - A. Kosyan; O. Smirnov; N. Taran; V. Burdyga (Vìsnik: Kiïvsʹkij Nacìonalʹnij Unìversitet Imenì Tarasa Ševčenka. Bìologìâ, 2017)
A new effective non-invasive method of screening of highly productive forms of buckwheat sowing (Fagopyrum esculentum Moench.) based on rapid testing of buckwheat seedling intensity exudation of organic acids root system in the laboratory is offered. Buckwheat seeds were germinated on agar gel layer which contains in its composition acid-base indicator followed by visual assessment of the indicator color changes around primary root and plants with the largest area of color change were selected. The effectiveness of the method was confirmed in the field conditions by phenotyping of plants and significant differences in determining the structure and yield performance of selected plants were found. Statistical analysis of indicators grain number and grain weight showed that these indicators in selected plants were over 6 times higher than in the control variant with the degree of reliability of 99%.